Cohort profile: Project on Human Development in Chicago Neighborhoods and its additions (PHDCN+) - Sampson, Robert J. (Journal of developmental and life-course criminology, 2022)
The Project on Human Development in Chicago Neighborhoods (PHDCN) began in the mid-1990s, using an accelerated longitudinal design and drawing a representative sample of over 6200 children from a total of seven birth cohorts (ages 0 to 18) living in Chicago. Participants were followed for a second and third wave of data collection ending in 1998 and 2002, respectively. Independent surveys and observations on Chicago neighborhoods were also conducted. In 2012, a random subsample from cohorts 0, 9, 12, and 15 was selected for further follow-up, resulting in 1057 wave 4 interviews. In 2021, a fifth wave was launched to locate and survey wave 4 respondents, resulting in 682 responses. The extension to waves 4 and 5, termed the PHDCN+, is the main focus of this cohort profile. Survey data were collected from many domains including, but not limited to, family relationships, exposure to violence and guns, neighborhood context, self-reported crime, encounters with the police, attitudes toward the law, health, and civic engagement. In addition, official criminal records were collected for 1995–2020. The resulting PHDCN+ data includes five waves of comprehensive survey data, residential histories, neighborhood contextual data, and criminal histories extending over 25 years for four cohorts differing in age by up to 15 years. The research design, measures, key findings from the cohort sequential design, and data access opportunities are discussed.